2016
DOI: 10.18632/oncotarget.9614
|View full text |Cite
|
Sign up to set email alerts
|

Technetium-99m-labeled rituximab for use as a specific tracer of sentinel lymph node biopsy: a translational research study

Abstract: PurposeWe aimed to develop and translate a CD20-antigen-targeted radiopharmaceutical, Technetium-99 m-labeled (99mTc) rituximab, for sentinel lymph node (SLN) detection.Methods99mTc-rituximab was synthesized and tested for stability in human serum. The binding affinity to CD20 was evaluated in Raji cells by flow cytometric analysis. Biodistribution and sentinel node mapping were carried out in bal b/c mice. Eighty-five patients with breast cancer participated in this study. Dynamic sentinel lymphoscintigraphy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In recent decades, a majority of studies have been devoted for developing novel, consistent SLN tracing methods, to reduce the FNR of SLNB, [ 12 ] resulting in the currently used methods of tracing SLNs: blue dye, [ 13 ] radioisotope, the combination of blue dye and isotope, [ 14 ] fluorescent dye, [ 15 , 16 ] and nanoparticles. [ 17 , 18 ] Though the novel methods of lymphoscintigraphy confer their own unique advantages in reducing the FNR of SLNB in preclinical studies, their application in practice depends upon further prospective clinical studies to identify suitable protocols, and the uptake of such advanced methods might require some time. [ 19 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, a majority of studies have been devoted for developing novel, consistent SLN tracing methods, to reduce the FNR of SLNB, [ 12 ] resulting in the currently used methods of tracing SLNs: blue dye, [ 13 ] radioisotope, the combination of blue dye and isotope, [ 14 ] fluorescent dye, [ 15 , 16 ] and nanoparticles. [ 17 , 18 ] Though the novel methods of lymphoscintigraphy confer their own unique advantages in reducing the FNR of SLNB in preclinical studies, their application in practice depends upon further prospective clinical studies to identify suitable protocols, and the uptake of such advanced methods might require some time. [ 19 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…It is also the target of Rituximab, one of the most effective antitumor monoclonal antibodies developed so far. Xuejuan Wang et al [7] has reported the preparation and use of 99m Tc-Rituximab for SLN detection in animal models and confirmed that it exhibits the desired properties of rapid clearance from the injection site as well as low accumulation in distal nodes. In this work, we carried out a clinical trial to confirm these characteristics in human subjects and to further compare the detection efficiency between 99m Tc-Rituximab and fTcSC.…”
Section: Introductionmentioning
confidence: 99%